Validation of leaf enzymes in the detergent and textile industries: launching of a new platform technology. Issue 6 (23rd April 2019) - Kumari, Uma; Singh, Rahul; Ray, Tui; Rana, Seema; Saha, Prasenjit; Malhotra, Karan; Daniell, Henry
Summary: Chemical catalysts are being replaced by biocatalysts in almost all industrial applications due to environmental concerns, thereby increasing their demand. Enzymes used in current industries are produced in microbial systems or plant seeds. We report here five newly launched leaf‐enzyme products and their validation with 15 commercial microbial‐enzyme products, for detergent or textile industries. Enzymes expressed in chloroplasts are functional at broad pH/temperature ranges as crude‐leaf extracts, while most purified commercial enzymes showed significant loss at alkaline pH or higher temperature, required for broad range commercial applications. In contrast to commercial liquid enzymes requiring cold storage/transportation, chloroplast enzymes as a leaf powder can be stored up to 16 months at ambient temperature without loss of enzyme activity. Chloroplast‐derived enzymes are stable in crude‐leaf extracts without addition of protease inhibitors. Leaf lipase/mannanase crude extracts removed chocolate or mustard oil stains effectively at both low and high temperatures. Moreover, leaf lipase or mannanase crude‐extracts removed stain more efficiently at 70 °C than commercial microbial enzymes (<10% activity). Endoglucanase and exoglucanase in crude leaf extracts removed dye efficiently from denim surface and depilled knitted fabric by removal of horizontal fibre strands. Due to an increased demand for enzymes in the food industry, marker‐free lettuce plants expressing lipase or cellobiohydrolase were created for the first time and site‐specific transgene integration/homoplasmy was confirmed by Southern blots. Thus, leaf‐production platform offers a novel low‐cost approach by the elimination of fermentation, purification, concentration, formulation and cold‐chain storage/transportation. This is the first report of commercially launched protein products made in leaves and validated with current commercial products.